Antioxidant, Anti-inflammatory, Antiproliferative and Antimicrobial Activities of Combretum glutinosum and Gardenia aqualla Extracts in vitro - Muhammad, Bawa Yusuf; Shaban, Nadia Zaky; Elrashidy, Fatima Hassan; Ghareeb, Doaa Ahmed (Free Radicals and Antioxidants)
Objectives: Plants represent a diverse template that could be tapped as sources of novel drugs. This study highlights antioxidant, anti-inflammatory, anti-proliferative and as well antimicrobial activities of Combretum glutinosum (BE) and Gardenia aqualla (GE) roots ethanol extracts. Methods: The Biological activities were evaluated using the established standard methods. Results: Both extracts exhibited antioxidant and anti-inflammatory activities with BE being better than GE. Anti-proliferative (cytotoxicity) assay on HepG2 and BHK-21 cell lines similarly revealed that BE (IC50: 55, SI: 1.81) is more cytotoxic and more selective than GE (IC50: 478.60, SI: 0.99). For the antimicrobial study, BE inhibited the growth of pathogenic bacteria; Pseudomonas aeruginosa, Staphylococcus aureus, Vibrio species and E. coli, while GE extract showed activity against Candida albicans. Conclusion: We conclude that Combretum glutinosum extract (BE) possessed the most robust activity from this study. Hence, it could be a promising source of novel drug with wide biological activities, especially antioxidant and anticancer activities.
Keywords: Antioxidant; Cytotoxicity; Cancer cell line; Anti-microbial; Drug discovery